2014
DOI: 10.1016/j.jviromet.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

FMDV replicons encoding green fluorescent protein are replication competent

Abstract: HighlightsFMDV replication can be studied outwith high disease secure facilities.FMDV replicon genomes encoding GFP are replication competent.These FMDV replicon systems can be used to study replication by live-cell imaging/image analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 18 publications
(23 reference statements)
0
46
0
Order By: Relevance
“…as a result of input translation only). Levels of GFP expression in GFP-pac-GNN replicon-transfected cells were similar to those with a second replication-deficient replicon, GFP-pac-D3D (Tulloch et al, 2014), with a large deletion in the 3D pol gene (data not shown).…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…as a result of input translation only). Levels of GFP expression in GFP-pac-GNN replicon-transfected cells were similar to those with a second replication-deficient replicon, GFP-pac-D3D (Tulloch et al, 2014), with a large deletion in the 3D pol gene (data not shown).…”
Section: Resultsmentioning
confidence: 56%
“…Development and use of the FMDV pGFP-pac-WT replicon construct has been described previously (Forrest et al, 2014;Tulloch et al, 2014). The replication-defective FMDV replicon, pGFP-pac-GNN, bearing a inactivating point mutation to the 3D pol active site was generated by standard PCR mutagenesis (Herod et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations